Effect of calcifediol supplementation on renin‐angiotensin‐aldosterone system mediators in dogs with chronic kidney disease - Matthew Miller; Jessica Quimby; Catherine Langston; Marisa Ames; Valerie J. Parker (Journal of Veterinary Internal Medicine, 2022)
Abstract Background Chronic kidney disease (CKD) leads to low serum concentrations of vitamin D metabolites. Thus, hypovitaminosis D associated with CKD might contribute to disease progression via increased concentration of renin angiotensin aldosterone system (RAAS) mediators. Objectives To evaluate whether supplementation with calcifediol affects equilibrium concentrations of selected mediators of the RAAS. We hypothesized that vitamin D supplementation will decrease concentration of circulating RAAS mediators in dogs with CKD. Animals Six client‐owned adult dogs with IRIS Stage 2 and 3 CKD. Methods Prospective study. Serum 25‐hydroxyvitamin D (25[OH]D), 1,25‐dihydroxyvitamin D (1,25[OH]2D), 24,25‐dihydroxyvitamin D (24,25[OH]2D), RAAS mediators (angiotensin I/II/III/IV/1‐5/1‐7, and aldosterone), and surrogate angiotensin converting enzyme (ACE) activity (calculated by the ratio of angiotensin II to angiotensin I) were evaluated at baseline, after 3 months of calcifediol supplementation, and 2 months after discontinuing administration of supplement. Results All serum vitamin D metabolite concentrations increased significantly by month 3 (P < .001): 25(OH)D (median 250 ng/mL; range, 204‐310), compared to baseline (median 43.2 ng/mL; range, 33.8‐58.3 ng/mL); 1,25(OH)2D (median 66.1 pg/mL; range, 57.3‐88.1 pg/mL) compared to baseline (median 35.2 pg/mL; range, 29.3‐56.7 pg/mL); 24,25(OH)2D (median 68.4 ng/mL; range, 22.1‐142.0 ng/mL) compared to baseline (median 14.4 ng/mL; range, 9.0‐21.3 ng/mL). Calculated ACE activity was significantly lower at month 3 (median 0.5; range, 0.4‐1.0) compared to baseline (median 0.7; range, 0.6‐1.3; P = .01). There were no significant differences in any of the evaluated RAAS variables at any other time‐point. Conclusions and Clinical Importance Short‐term calcifediol supplementation in this small group of CKD dogs appeared to decrease ACE activity.